Botne, Robert (with Hannington Ochwada and Michael Marlo) 2006. A Grammatical Sketch of the Lusaamia Verb. Rüdiger Köppe Verlag: Köln - Drolc, Ursula (AAeO - Afrikanistik-Aegyptologie-Online, 2007)
Lusaamia (Ólusaamya) is spoken in western Kenya and eastern Uganda. It belongs to the Luluyia dialect cluster and is classified as E.34 in Guthrie’s (1967-71) zone classification and J.34 in the Tervuren (1978) revision of Guthrie. Related dialects are Bukusu, Lutsootso, Lukisa, Lulogooli, and Lunyole spoken in Kenya. Only a few articles have been written on this language. They deal with specific tonological, phonological and morphological issues such as reduplication or segmental duration.